Offer og initiation i vedisk religion - Erik Reenberg Sand (Religionsvidenskabeligt Tidsskrift, 1995)
After a short presentation of various scholarly views regarding the affinity between initiation and sacrifice in general, the present paper investigates various parallels on the structural, the formal and the symbolic level between the Vedic student (brahmacari) and the consecrated sacrificer (diksita) of the Vedic soma-sacrifice. Especially it is shown how both the upanayana and the Vedic consecration (diksa) transform the Vedic student and the sacrificer into an embryonical state, which, most evident in the case of the sacrificer, is connected with symbols of death and self sacrifice, and how both initiation and sacrifice are seen as a symbolic rebirth by help of sacred knowledge (brahman). On this basis it is concluded that the Vedic Soma sacrifice, containing elements of death, rebirth and knowledge, thus seems to have much in common with initiation, but neverthelss one should be careful not to draw too hasty general conclusions because of the special nature of the Vedic material.